Diatom assemblages from sediment traps in response to large seaweed Gracilaria cultivation off Nan'ao island, South China. (April 2021) - Lei, Yuanda; Feng, Peijun; Du, Xiaoqin; Jiang, Shijun
Abstract: Most previous studies on seaweed bioremediation largely focus on laboratory control tests or short-time, in-situ field experiments. Here we present a dataset from 4-year-long field monitoring (2014–2018) in a mariculture area of the Baisha Bay off Nan'ao Island, South China, attempting to examine how the large seaweed Gracilaria lemaneiformis cultivation affects a mariculture ecosystem. The temporal variation in seawater physicochemical properties (TN, TP, Reactive silicate, CODMn, and chlorophyll α) and sediment proxies (TN and TP) suggest that the Baisha Bay maintained a better water quality during the Gracilaria cultivation periods (December–May) than other months. Additionally, sedimentary diatom assemblages during the Gracilaria cultivation periods showed an increase in Shannon-Wiener values, but a decrease in the dominant Thalassionema nitzschioides abundance, total diatom abundances and P/(A + B) ratios [Planktonic/(Attached + Benthic)]. These changes consistently suggest that Gracilaria cultivation may have helped improve seawater quality and phytoplankton diversity, thereby maintain a healthy mariculture ecosystem. Highlights: Produce a dataset from 4-year-long field monitoring (2014–2018) in a mariculture area off Nan'ao Island, South China. Investigate the temporal variation in seawater physicochemical properties and sediment nutrients and diatom assemblages. Reveal better water quality during the Gracilaria cultivation periods (December-May) than other months. Sedimentary diatom assemblages show higher Shannon-Wiener values and lower biomass during the Gracilaria cultivation periods.